Family career success indicators as tools for literacy sustainability among urban youths in the Ibadan metropolis (2019)
This study examined family career success indicators in relation to literacy sustainability among urban youths in Ibadan. The study adopted a descriptive design of the correlational type. Through the convenience sampling approach, 300 male and female youths in Ibadan city within the ages of 17 and 25 years were sampled. Self-efficacy, employability; personality, life satisfaction, career counselling and social recognition scales were adapted for data collection. Data was computed using Pearson Product Moment Correlation. The result showed that self-efficacy, employability, personality, life satisfaction, career counselling and social recognition predicted family career success among the urban youths in Ibadan. It was concluded that family career success is critical for literacy sustainability. It was therefore recommended that adequate and regular awareness on career success indicators be intensified among urban youths, if literacy will be sustained in Nigeria. For urban youths to be interested in literacy skill development, family career success and its indicators should be seen as catalysts